Phenolic compounds from Andean mashua (Tropaeolum tuberosum) tubers display protection against soybean oil oxidation - Betalleluz-Pallardel I. (2012)
Phenolic compounds from mashua tuber were evaluated as potential antioxidants to retard the oxidation of crude soybean oil submitted to accelerated storage and frying. During the accelerated storage, an ethanolic crude extract, a purified extract, an aqueous fraction and an ethyl acetate fraction from mashua containing different gallic acid equivalent concentrations (100, 300 and 600 ppm) in oil were evaluated at 55 C. After 15 days of storage, better effects were evidenced against soybean oil oxidation at 300 and 600 ppm of ethyl acetate fraction in comparison to 200 ppm butylated hydroxytoluene and the control (no antioxidant added). During the frying process at 180 C, principal component analysis revealed that the content of trienes and dienes were strongly correlated with the frying batch. Ethyl acetate fraction at 200 ppm showed the highest efficacy against oil oxidation in terms of polar compound values, free fatty acids and conjugated dienes and trienes in comparison to the oil containing 200 ppm tert-butylhydroquinone and control. Differential scanning calorimetry corroborated the efficacy of ethyl acetate fraction phenolic and it is strongly recommended as method for validation of results. This study provides strong evidence related to the excellent protective effects against soybean oil oxidation of mashua phenolics. This crop could be utilized as an alternative source of natural antioxidants by the oil industry